2004
DOI: 10.1111/j.1600-6143.2004.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Influence of the Interleukin-6 Promoter Polymorphisms –597, –572 and –174 on Long-Term Kidney Allograft Survival

Abstract: Recently, we demonstrated an association of the IL-6 promoter polymorphism at position -174 (G→C) with kidney allograft survival whereby carriers of the −174GG genotype were identified as having superior graft survival. As two additional polymorphisms were discovered in the neighborhood at positions −572 (G→C) and −597 (G→A), respectively, and as functional studies revealed a cooperative impact of all three on the IL-6 gene transcription, we investigated whether there is a combined effect on kidney transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 19 publications
8
37
0
Order By: Relevance
“…Considering that most of our patients suffered from developmental dysplasia of the hip (DDH), this may indicate an association between IL-6 promoter SNPs and DDH. Combination of genotypes G/G | G/G | G/G at -597, -572 and -174 appears to be predictive for a better kidney allograft survival: it is associated with lower hazard of allograft rejection than other combinations taken cumulatively 28 . In the current report, individual influences of the IL-6 (-597) and (-572) sites/genotypes did not appear to have 15 a relevant effect on the prosthesis survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that most of our patients suffered from developmental dysplasia of the hip (DDH), this may indicate an association between IL-6 promoter SNPs and DDH. Combination of genotypes G/G | G/G | G/G at -597, -572 and -174 appears to be predictive for a better kidney allograft survival: it is associated with lower hazard of allograft rejection than other combinations taken cumulatively 28 . In the current report, individual influences of the IL-6 (-597) and (-572) sites/genotypes did not appear to have 15 a relevant effect on the prosthesis survival.…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies have demonstrated complex interactions among these sites in the regulation of IL-6 transcription 15 . A complete linkage disequilibrium between (-597G→A) and (-174G→C) sites 16,[25][26][27][28] , and no disequilibrium 16,25,26,28 or a complete negative disequilibrium 27 between (-597G→A) and (-572G→C) sites have been reported in European populations. 15,28 indicate -597/-572 haplotypes GG (around 50%) and AG (around 40%) as the most prevalent ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An ex-vivo functional study [25] demonstrated that the GGG haplotype of the IL6 promoter produces more IL-6 than other promoter haplotypes. Whether carriers of the GGG haplotype also secrete more IL-6 under physiological in-vivo conditions [26] is, however, unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that these three SNPs (−174, −572, −597) of the IL6 promoter do not act independently in the regulation of IL6 transcription [25][26][27]. In a study of lipopolysaccharidestimulated IL-6 production by leucocytes it was demonstrated that leucocytes from the homozygous carrier of the GGG-haplotype (−597 GG, −572 GG and −174 GG) produced the highest amount of IL-6 [25].…”
Section: Introductionmentioning
confidence: 99%